Предмет: Алгебра, автор: luna61

Решите (cos(2pi-t)sin^2(3pi/2-t))/(tg^2(t-pi/2)cos^2(t-3pi/2))

Ответы

Автор ответа: fse13
0

(cos(2pi-t)sin^2(3pi/2-t))/(tg^2(t-pi/2)cos^2(t-3pi/2))

по формулам приведения:

cos(2pi-t)=Cos(t)

sin^2(3pi/2-t)=Cos²(t)

tg^2(t-pi/2)=ctg²(t)

cos^2(t-3pi/2)=Sin²(t)

подставляем:

(Cos(t)*Cos²(t))/(ctg²(t)*Sin²(t))

по формуле приведения:

Cos²(t)/Sin²(t)=ctg²(t)

поставляем:

Cos(t)/ctg²(t) * ctg²(t)

сокращаем ctg²(t)

остается Cos(t)

(cos(2pi-t)sin^2(3pi/2-t))/(tg^2(t-pi/2)cos^2(t-3pi/2))=cos(t)

 

Похожие вопросы
Предмет: Математика, автор: zydmydrosti42